Borgerinddragelse, videnskab og ekspertise: Deliberation om biodiversitet - Jæger, Birgit (Politik, 2014)
How is scienti c knowledge and experience of laypeople mixed when citizens participate in public engage- ment events? Drawing on an STS approach to ‘scienti c citizenship’ and ‘socially robust knowledge’, and an approach to ‘deliberative democracy’, this paper presents an analysis of how scienti c knowledge was pre- sented and used by citizens participating in a global hearing on biodiversity in 2012. e analysis shows that the presented scienti c knowledge, together with the themes of discussion, framed the deliberation among the citizens in a way that made it di cult for them to enact scienti c citizenship. However, due to a shared belief that citizens are responsible for their actions, the citizens managed to add their own perspective, based on their experience and values, to the scienti c knowledge and in this way they contributed to the process of creating socially robust knowledge.